2019
DOI: 10.3390/agronomy9100628
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flooding or Alternate Wetting and Drying Differently Affect the Accumulation of Health-Promoting Phytochemicals and Minerals in Rice Brown Grain

Abstract: Climate changes impose adoption of water-saving techniques to improve the sustainability of irrigated rice systems. This study was aimed, by a two-years side-by-side comparison, at verifying the hypothesis whether “Alternate Wetting and Drying” (AWD) affects the concentrations of health-related compounds and minerals in brown grains of three japonica rice (Oryza sativa L.) cvs (‘Baldo’, ‘Gladio’, and ‘Loto’) usually grown in temperate areas in continuous flooding (CF). Due to the rotational turns in water dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…There were studies pointing that the varying water management affecting on bioactive compounds in rice. Orasen et al (2019) reported that water regimes by alternate wetting and drying stimulated the biosynthesis of flavonoid in brown rice grain of non- Table 3. Significant effects of variety, water and year on the concentration of anthocyanin, Zn and Fe in the grain and yield of 11 purple rice varieties grown in aerobic and wetland conditions in 2012 and 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were studies pointing that the varying water management affecting on bioactive compounds in rice. Orasen et al (2019) reported that water regimes by alternate wetting and drying stimulated the biosynthesis of flavonoid in brown rice grain of non- Table 3. Significant effects of variety, water and year on the concentration of anthocyanin, Zn and Fe in the grain and yield of 11 purple rice varieties grown in aerobic and wetland conditions in 2012 and 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2014) reported that alternate wetting and drying (AWD) significantly increased Zn concentration and grain yield. On the other hand, AWD positively affected on antioxidant compounds in brown rice but negatively affect on grain Zn (Orasen et al, 2019). However, the impact of water regimes on nutritional qualities anthocyanin, Zn and Fe as well as grain yield among the purple rice varieties has not been well informed so far.…”
Section: Introductionmentioning
confidence: 99%
“…Under these flooded conditions, As is more readily released from the solid phase, becoming available for uptake by plants. Aerobic conditions are created when fields are left to desaturate before reflooding; these practices can also effectively reduce As accumulation ( Orasen et al, 2019 ). AWD practices also benefit water conservation efforts and lessen greenhouse gas emissions in rice production ( Linquist et al, 2015 ; Setyanto et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the DSI management system, the DSF system shows a reduction of about − 10% for all impact categories compared to this case study, while in the WSF system, the variation in impacts is greater than in the other water management systems (thus being less sustainable compared to VRP, DSF, and DSI), and this could be related to rice growing conditions. In fact, in this water management system, excluding a short period to allow for weed control, the paddy field is kept under constant flooding until pre-harvest drainage (Orasen et al 2019). The sensitivity analysis thus shows how the use of the DSI management system could significantly reduce environmental impacts, in most categories by halving them, compared to the system used in this case study.…”
Section: Sensitivity Analysismentioning
confidence: 89%